Development of Hydro-Meteorological Hazard Early Warning System in Indonesia - Armi Susandi; Mamad Tamamadin; Alvin Pratama; Irvan Faisal; Aristyo R. Wijaya; Angga F. Pratama; Olgha P. Pandini; Destika Agustina Widiawan (Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
This paper discusses the result of the development of a hydro-meteorological hazard early warning system (H-MHEWS) that combines weather prediction from Weather Research and Forecasting (WRF) and the hydrometeorological hazard index from the National Disaster Management Authority (BNPB), Indonesia. In its current development phase, the hazards that H-MHEWS predicts are floods, landslides, and extreme weather events. Potential hazard indices are obtained by using an overlay approach and resampling so that the data have a 100-m spatial resolution. All indices are classified into 4 status categories: